On Several Types of Continuity and Irresoluteness in L-Topological Spaces - Al Ghour, Samer H. (Kuwait Journal of Science, 2018)
We use the concepts of ω-open L-sets, N-open L-sets and D-open L-sets to define several new types of continuity or irresoluteness in L-topological spaces. Several results are given. In particular, decomposition theorems of the new irresoluteness concepts are introduced.